2021
DOI: 10.4300/jgme-d-21-00217.1
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy in the Operating Room: A Multicenter Study of Gender Disparities During Surgical Training

Abstract: Background Gender disparities are prevalent in medicine, but their impact on surgical training is not well studied. Objective To quantify gender disparities in trainee intraoperative experiences and explore the variables associated with ratings of surgical autonomy and performance. Methods From September 2015 to May 2019, attending surgeons and trainees from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…In this study, resident gender was not associated with either attending evaluations or resident self‐assessments. This is particularly interesting because in previous studies pooling SIMPL OR data across surgical specialties, trainee gender was found to be a source of disparities in attending ratings of surgical autonomy and performance 16 . Many other studies using a range of self‐assessment instruments have also found that female residents are more self‐critical than male residents 16–18 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this study, resident gender was not associated with either attending evaluations or resident self‐assessments. This is particularly interesting because in previous studies pooling SIMPL OR data across surgical specialties, trainee gender was found to be a source of disparities in attending ratings of surgical autonomy and performance 16 . Many other studies using a range of self‐assessment instruments have also found that female residents are more self‐critical than male residents 16–18 .…”
Section: Discussionmentioning
confidence: 90%
“…This is particularly interesting because in previous studies pooling SIMPL OR data across surgical specialties, trainee gender was found to be a source of disparities in attending ratings of surgical autonomy and performance. 16 Many other studies using a range of self-assessment instruments have also found that female residents are more self-critical than male residents. [16][17][18] One possible explanation for the difference in findings between this multicenter study of otolaryngology residents compared to studies that pooled data across surgery programs nationwide could be the nearly equal numbers of male and female trainees in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple recent singleand multicenter studies demonstrate that women get less operative autonomy as trainees. [28][29][30][31] One study conducted in 2019 reviewed almost 9,000 cases at 14 general surgery programs and found that female surgical residents received less operative autonomy even when controlled for training level, case complexity, faculty sex, and program environment. This gap in autonomy was seen at every level of training and was most pronounced in the fourth year of training, which is when most trainees experience autonomy in intraoperative decision making and patient care.…”
Section: Operative Opportunities and Autonomymentioning
confidence: 99%
“…Chen et al report a multicenter review of nearly 95 000 assessments and identified the development of a gap in autonomy ratings for women over the course of surgical trainees, with the largest gap occurring in the most complex cases. 5 Additionally, women trainees self-rated as having less autonomy and worse performance than men, even after controlling for most other potential confounding elements. Cooney et al's review of 8377 assessments of plastic surgery residents in 3 different programs found women trainees were scored significantly lower than men in the first 4 years of residency when rated by men attending surgeons, but not when rated by women attending surgeons.…”
mentioning
confidence: 99%